Pengaruh Model Pembelajaran Kooperatif Tipe Jigsaw untuk Meningkatkan Berpikir Tingkat Tinggi Siswa di Kelas V - Rifa’ul Khulqi; Nurdinah Hanifah; Cucun Sunaengsih (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
Conventional learning activities have an impact on learning outcomes which are still low, therefore it is important to choose the right learning model to improve students' high-level thinking abilities. The research aims to improve the learning model for learning outcomes, so it is necessary to apply the jigsaw type cooperative learning model to improve students' high-level thinking abilities as a form of learning outcomes in the material forms of human interaction with the science and science environment in class V of SDN Tegalkalong. This research method uses a design (quasi-experimental) which involves two classes, a control class using a conventional model with 30 students and an experiment using a cooperative jigsaw type model with 30 students from class V at SDN Tegalkalong. Use descriptions of pretest questions to determine initial abilities and posttests to measure final abilities of learning outcomes. In the final test results after implementing the science and science learning model in the control and experimental classes, the average score of the students experienced a difference in the learning outcomes that were treated with the jigsaw type cooperative learning model, which had a higher average score (100), whereas compared to conventional class learning outcomes, it had average value (80). This research provides benefits to students involved in the research as well as insight to teachers as a reference in implementing the learning model that has been implemented which can have a positive influence. This criterion shows the success of using the jigsaw type cooperative learning model which is very suitable for application at the elementary school level in improving high-level thinking skills as a form of learning outcome.